2022
DOI: 10.2147/jir.s345108
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Protects Against Sepsis-Associated Encephalopathy-Induced Learning and Memory Deficits by Enhancing the Synthesis and Release of Vasopressin in the Supraoptic Nucleus

Abstract: Background As a severe complication of sepsis, sepsis-associated encephalopathy (SAE) usually manifests as impaired learning and memory ability in survivors. Previous studies have reported that environmental enrichment (EE) can increase the learning and memory ability in different brain injury models. However, there has been no research on the possible positive effect of EE on SAE. Aim The present study aimed to test the effect of EE on SAE-induced impairment of learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…In the present study, SAE induced significant increases in the levels of TNF-α, IL-6, and IL-1β in the brain, which further confirmed the role of neuroinflammation in SAE-induced cognitive dysfunction. Interestingly, our recent study showed that the hippocampal TNF-α content between Sham-SE, SAE-SE, and SAE-EE rats did not change [9]. We propose that neither an environmental factor nor a SAE factor influenced the hippocampal TNF-α level, suggesting that TNF-α is not involved in SAE-induced deficits in spatial learning and memory.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In the present study, SAE induced significant increases in the levels of TNF-α, IL-6, and IL-1β in the brain, which further confirmed the role of neuroinflammation in SAE-induced cognitive dysfunction. Interestingly, our recent study showed that the hippocampal TNF-α content between Sham-SE, SAE-SE, and SAE-EE rats did not change [9]. We propose that neither an environmental factor nor a SAE factor influenced the hippocampal TNF-α level, suggesting that TNF-α is not involved in SAE-induced deficits in spatial learning and memory.…”
Section: Discussionmentioning
confidence: 63%
“…Housing conditions comprising social interactions, novelty, and various forms of exercise are referred to as environmental enrichment (EE). Numerous studies have reported the positive effect of EE on cognitive function under various brain injuries [9]. For example, EE can improve the sensory and memory ability for traumatic brain injury (TBI) rats by changing the levels of proinflammatory cytokines and anti-inflammatory cytokines [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the present study found that EE pre-exposure counteracted the IE-induced change in inflammatory mediators in the hippocampus, suggesting a positive effect of EE on the learning and memory ability under IE conditions. In fact, it has been reported that EE affects cytokines, various immune components, and glial cells under various pathological conditions [ 24 , 56 58 ]. The antineuroinflammatory effect of EE might be achieved through several immune pathways [ 59 , 60 ]: (i) increased migration of macrophages into the CNS and enhancement of their regulatory effects on microglia; (ii) upregulation of mitogen-activated protein kinase (MAPK) phosphatase-1 (MKP-1), which exhibits negatively regulatory roles in proinflammatory macrophage MAPK activation; and (iii) modulation of hippocampal T cells, which are responsible for the modulation of microglia.…”
Section: Discussionmentioning
confidence: 99%
“…EE: Rats were housed in a large cage (40 cm ×54 cm ×30 cm) with six rats per cage. As previously described, the cages contained multiple objects including wooden blocks, plastic bone-shaped toys, a running wheel, and a plastic tunnel [ 24 ]. Suspended ropes allowed for climbing from one level to another.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation